2021
DOI: 10.1111/jfpp.15959
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of bioactive compounds and antioxidant activity in bananas during ripening

Abstract: The study aimed to characterize bananas in their different stages of ripeness, to determine the variables that demonstrate higher levels at each moment. The fruits were analyzed according to physical parameters: weight, texture, and diameter of the fruits; as well as physicochemical parameters: pH, titratable acidity, soluble solids, and Ratio; and also biochemical parameters: total sugars, phenolic compounds, ascorbic acid, pigments, antioxidant activity by DPPH and FRAP methods. The used samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…When studying “Nanicão” bananas, Souza et al. (2021) found superior levels of ascorbic acid in overripe fruits with maximum values of 1.2 µg g −1 . Watharkar et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying “Nanicão” bananas, Souza et al. (2021) found superior levels of ascorbic acid in overripe fruits with maximum values of 1.2 µg g −1 . Watharkar et al.…”
Section: Resultsmentioning
confidence: 99%
“…Ascorbic acid is an important antioxidant in the removal of reactive oxygen species and regeneration of α-tocopherol (Jimenez et al, 2002). When studying "Nanicão" bananas, Souza et al (2021) found superior levels of ascorbic acid in overripe fruits with maximum values of 1.2 µg g −1 . Watharkar et al (2010) reported an increase of almost 90% in the ascorbic acid content of Musa nana Lour versus Dwarf Cavendish bananas, with values ranging from 0.67 µg g −1 for unripe fruits to 1.3 µg g −1 for ripe fruits.…”
Section: Quantification Of Ascorbic Acid and Flavonoidsmentioning
confidence: 99%
“…When there was no interaction between the factors, comparisons were made between the means only of the factor levels that showed a significant difference in ANOVA. A confidence level of 5% was considered in all statistical tests [88] and the R software [89] was used for the application of the described tests.…”
Section: Analyses Statisticsmentioning
confidence: 99%
“…Titratable acidity was expressed in grams of citric acid per 100 g of pulp (g of citric acid 100 g −1 ). The quantification is obtained by titrating 5 g of homogenized and diluted pulp to 100 mL of distilled water, with standardized 0.1 N sodium hydroxide solution, with phenolphthalein used as the indicator [18,19].…”
Section: Titratable Acidity (Ta)mentioning
confidence: 99%